P13 Exhaled nitric oxide and blood eosinophil count in predicting sputum inflammatory type in a heterogeneous airways disease population. (12th November 2019) - Lehtimäki, L; Shrimanker, R; Moran, A; Hynes, G; Thulborn, S; Borg, C; Connolly, C; Gittins, A; Downs, T; Russell, R; Brightling, C; Cane, J; et al.
Abstract : Background: Exhaled nitric oxide (FeNO) and blood eosinophil count (B-eos) correlate with sputum eosinophil count in asthma and COPD, and cut-off values have been introduced to help decision making. However, these cut-off values have not been validated in large heterogeneous clinical cohorts. Our aim was to assess in a real life mixed airways disease population the abilities of currently recommended cut-off values of FeNO, blood eosinophil count and their combinations to predict the presence of airway inflammation as reflected by sputum eosinophil and neutrophil count. Methods: We recruited 310 subjects with obstructive airway disease (260 with asthma, 50 with COPD) from a tertiary referral centre. Induced sputum cell differentials, FeNO, B-eos and spirometry were measured. FeNO and B-eos were categorised as low (<25 ppb and <0.150 x 10 9 cells/L), intermediate (25–50 ppb and 0.15 – 0.29 x 10 9 cells/L) and high (>50 ppb and ≥0.3 x 10 9 cells/L), respectively. A composite variable of FeNO and B-eos was formed with four categories as follows: both high, either high, both low, and all other combinations. We assessed the ability of FeNO, B-eos and their composite to predict the presence of sputum eosinophilia (≥3%) and neutrophilia (>61%). Results: The majority of subjects were on maintenance ICS (84.2%) and/or LABA (73.9%) and smaller proportions on LAMA (26.1%) and oral corticosteroids (16.1%). Both FeNO and B-eos were better in predicting sputum eosinophilia than in predicting neutrophilia. Having both FeNO and B-eos high was associated with an 80.4% probability of having sputum eosinophilia and a 25.5% probability of having sputum neutrophilia. On the other hand, having both FeNO and B-eos low was associated with a probability of only 2.9% of having sputum eosinophilia and a 61.8% probability of having sputum neutrophilia (Figure 1). B-eos performed equally well in subjects with asthma or COPD while FeNO performed better in subjects with asthma. Conclusion: Currently recommended cut-off values of FeNO and B-eos have good ability to predict presence or absence of sputum eosinophilia in a mixed group of subjects with airways disease. These markers in combination also have a moderate ability to predict presence or absence of sputum neutrophilia.